IMPLEMENTASI GOOD GOVERNANCE PENGADAAN BARANG DAN JASA PADA MASA PANDEMI COVID-19 DI DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN KOTA METRO - Abbas Abbas; Farida Farida; Dany Suryawan (e-JKPP, 2021)
The procurement of goods and services is part of the management of state finances so that good governance arrangements are needed in accordance with Good Governance. The procurement of goods and services also plays an important role in the implementation of development both nationally and regionally in order to improve public services. This research was conducted using qualitative methods and data obtained by means of observation and interviews with twenty informants who are involved in the procurement of goods and services. Data were analyzed by reducing data, presenting data, interpreting and drawing conclusions.The results obtained are that the COVID-19 pandemic has greatly affected the procurement of goods and services, especially in terms of the budget which resulted in the failure of the procurement of goods and services in the first semester. In terms of applying the principles of Good Governance, the results show that in general the process of procurement of goods and services at the Department of Housing and Settlement Areas of Metro City has implemented the principles of Good Governance, it's just that there are some principles that cannot be applied optimally. For this reason, so that the application of the principles of Good Governance can be applied as a whole and maximally, it requires serious effort or determination from the power holder or office holder to eliminate interests that can interfere with the process of procuring goods and services to the government.